2016
DOI: 10.1128/aem.04103-15
|View full text |Cite
|
Sign up to set email alerts
|

Killing of Staphylococcus aureus via Magnetic Hyperthermia Mediated by Magnetotactic Bacteria

Abstract: e Staphylococcus aureus is a common hospital and household pathogen. Given the emergence of antibiotic-resistant derivatives of this pathogen resulting from the use of antibiotics as general treatment, development of alternative therapeutic strategies is urgently needed. Here, we assess the feasibility of killing S. aureus cells in vitro and in vivo through magnetic hyperthermia mediated by magnetotactic bacteria that possess magnetic nanocrystals and demonstrate magnetically steered swimming. The S. aureus su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 26 publications
0
42
0
Order By: Relevance
“…With the discovery of MTB-grazing protozoa, we can envision a synthetic magnetization with the cocultivation of MTB with heterotrophic protozoa. This could be very useful for the sequestration of magnetosomes and their concentration into individual eukaryotic cells and might significantly improve some medical applications (e.g., drug delivery) that have been so far developed using cultured MTB (53)(54)(55). Heterotrophic bacteriovorus U. marinum and related species have been cultivated for years and are available in culture collections (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…With the discovery of MTB-grazing protozoa, we can envision a synthetic magnetization with the cocultivation of MTB with heterotrophic protozoa. This could be very useful for the sequestration of magnetosomes and their concentration into individual eukaryotic cells and might significantly improve some medical applications (e.g., drug delivery) that have been so far developed using cultured MTB (53)(54)(55). Heterotrophic bacteriovorus U. marinum and related species have been cultivated for years and are available in culture collections (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…[35,36] However, the number of works on magnetic hyperthermia performance of the "whole" magnetotactic bacteria is very limited. Song et al [37] found that magnetotactic bacteria under an external alternating magnetic field (AMF) can be used to kill Staphylococcus aureus, a common hospital and household pathogen. And Alphandéry et al [26] showed that intact bacterial cells containing chains of magnetosomes exhibit high specific absorption rates (SARs) of 625 W g −1 at 880 Oe and 108 kHz.…”
Section: Magnetic Hyperthermiamentioning
confidence: 99%
“…Magnetotactic bacteria can be constructed as drug-carrier microrobots [15,16]. Applying an alternating magnetic field to induce magnetic hyperthermia of magnetotactic bacteria is an alternative [22,23]. However, these applications generally needs two sets of independent devices that can generate guiding and alternating magnetic fields respectively.…”
Section: Introductionmentioning
confidence: 99%